An exceed 60% efficiency Nd:YAG transparent ceramic laser with low attenuation loss effect - Chang, Jin-Quan; Shen, Yu; Bian, Qi; Zong, Nan; Lv, Ze; Bo, Yong; Peng, Qin-Jun (Frontiers in Physics, 2022)
Here, the attenuation loss effect and laser performance enhancement of Nd:YAG transparent ceramics were investigated. Using a 0.6 at.% Nd:YAG ceramic rod of 3 mm diameter and 65 mm length, the scattering coefficient and absorption coefficient at 1,064 nm were measured to be 0.0001 cm−1 and 0.0017 cm−1, respectively. For the 808-nm side-pumped laser experiment, an average output power of 44.9 W was achieved with an optical-to-optical conversion efficiency of 26.4%, which was nearly the same with that of a 1 at% single crystal. Adopting the 885-nm direct end-pumped scheme, the following laser tests demonstrated a high optical efficiency of 62.5% and maximum output power of 144.8 W obtained at an absorbed pump power of 231.5 W. This was until now the highest optical conversion efficiency acquired in an Nd:YAG ceramic laser to our knowledge. It proves that high-power and high-efficiency laser output could be generated by a high-optical quality Nd:YAG ceramic rod along with the 885-nm direct pumping technology.